Gas diffusion electrode capable of efficiently producing hydrogen peroxide in situ and preparation method of gas diffusion electrode

By loading the catalyst layer and the gas diffusion layer on the hydrophobic carbon paper electrode, a gas-liquid solid three-phase electrode with a "sandwich" structure is solved, and the problems of low efficiency and poor electrode stability in the traditional electrochemical synthesis of hydrogen peroxide are achieved. Efficient and stable hydrogen peroxide production.

CN119287407APending Publication Date: 2025-01-10LIAONING UNIVERSITY
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411399577.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

In the process of traditional electrochemical synthesis of hydrogen peroxide, there is a problem of low efficiency, poor selectivity, high energy consumption, and easy flooding of electrodes and short life.

Method used

Hydrophobic carbon paper is used as the substrate, and the catalyst layer and gas diffusion layer are supported on both sides of the catalyst layer. The catalyst layer is made of a mixture of carbon nanotubes, g-C3N4, isopropanol and PTFE emulsion. The gas diffusion layer is composed of carbon black and PTFE emulsion. The ultrasonic immersion method is uniformly covered to form a gas-liquid solid three-phase electrode with a "sandwich" structure.

Benefits of technology

The yield and current efficiency of hydrogen peroxide are significantly improved, the current efficiency reaches 76%, the energy consumption is reduced to 5.56KWh/Kg, and the electrode stability and life are also improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119287407A_ABST
    Figure CN119287407A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electrochemistry, and particularly relates to a gas diffusion electrode for efficiently producing hydrogen peroxide in situ and a preparation method thereof. The gas diffusion electrode is composed of a carbon paper substrate, a carbon black gas diffusion layer and a carbon nitride modified carbon nanotube catalyst layer. The preparation method of the gas diffusion cathode comprises the following steps: mixing a carbon nanotube, g-C3N4, isopropanol, 60wt% of PTFE emulsion and water to prepare a mixed solution, and loading a compound of the carbon nanotube and g-C3N4 on one side of a carbon paper substrate by adopting an ultrasonic impregnation mode to prepare a catalyst layer; the other side of the carbon paper substrate is impregnated with carbon black and PTFE emulsion to prepare a diffusion layer, and the diffusion layer is uniformly coated, dried and annealed to prepare the gas diffusion cathode. The gas diffusion electrode is used for efficiently producing hydrogen peroxide through in-situ electrocatalysis, the yield of hydrogen peroxide can reach 1050 mg / L after 1.5 h, the current efficiency is 76%, and the energy consumption is 5.56 KWh / Kg.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrochemistry, and in particular relates to a gas diffusion electrode for in-situ efficient production of hydrogen peroxide and a preparation method thereof. Background Art

[0002] In the field of electrochemistry, hydrogen peroxide (H2O2) is an important redox species with wide applications in various industrial and medical applications.

[0003] The preparation of hydrogen peroxide usually involves electrochemical methods, which can efficiently produce hydrogen peroxide through the oxygen reduction reaction (ORR). However, traditional electrochemical synthesis processes are usually limited by low efficiency, poor selectivity, and high energy consumption. To overcome these challenges, gas diffusion electrode technology has been widely used in the efficient production of hydrogen peroxide. As one of the key components for producing hydrogen peroxide with high efficiency and selectivity, it has attracted extensive research and application.

[0004] Conventional electrolytic methods for producing redox species such as hydrogen peroxide are often limited by mass transfer limitations and efficiency losses in the electrochemical process. However, gas diffusion electrodes can significantly improve these problems by optimizing the way gas is transported. Their core function is to form a stable gas diffusion layer in the electrolyte solution through specially designed pore structures and material selection. This layer can effectively transfer oxygen from the gas phase to the electrolyte liquid phase, thereby increasing the rate and efficiency of the redox reaction. Specifically, gas diffusion electrodes can optimize the oxygen transfer path, reduce mass transfer resistance, and provide a stable and uniform reaction environment, which is critical for the efficient generation of hydrogen peroxide.

[0005] In the electrochemical production of hydrogen peroxide, the application of gas diffusion electrodes is not limited to improving the yield and efficiency, but also can control the selectivity of the reaction and the purity of the product. This is crucial for many industrial processes and medical applications, such as environmental treatment, sanitary disinfection, biomedicine and other fields. In practical applications, in order to achieve efficient hydrogen peroxide production, researchers often adjust the structure and materials of the gas diffusion electrode and optimize the composition and operating conditions of the electrolyte solution to achieve the best electrochemical performance. This includes not only the selection of appropriate electrode materials, such as carbon paper, carbon cloth or metal oxides, but also the design of optimized electrode structures, such as microporous structures and surface modifications, to improve the efficiency of gas diffusion and the selectivity of the reaction.

[0006] Therefore, developing a gas diffusion electrode that can efficiently generate hydrogen peroxide in situ involves not only the selection and design optimization of electrode materials, but also requires a deep understanding and optimization of various influencing factors in the gas transfer process. This technological advancement will provide more reliable and efficient solutions for related applications in the field of electrochemistry, and promote the widespread application and further research of hydrogen peroxide and its derivatives. Summary of the invention

[0007] The purpose of the present invention is to overcome the problems of low hydrogen peroxide yield, low current efficiency and unstable gas supply to the electrode gas diffusion layer of the unimproved electrode, and also solve the problem of easy flooding and short life of the electrode.

[0008] The technical solution adopted by the present invention is:

[0009] A gas diffusion electrode for in-situ efficient production of hydrogen peroxide uses hydrophobic carbon paper as a substrate, and a catalyst layer and a gas diffusion layer are respectively loaded on both sides of the hydrophobic carbon paper; the catalyst layer is a mixture of carbon nanotubes, g-C3N4, isopropanol, PTFE emulsion and water loaded on one side of the hydrophobic carbon paper; the gas diffusion layer is a mixture of carbon black and PTFE emulsion loaded on the other side of the hydrophobic carbon paper.

[0010] Preferably, in the above-mentioned gas diffusion electrode for in-situ efficient production of hydrogen peroxide, the mass fraction of PTFE in the PTFE emulsion is 60%.

[0011] Preferably, in the above-mentioned gas diffusion electrode for in-situ efficient production of hydrogen peroxide, the thickness of the hydrophobic carbon paper is 10-100 microns.

[0012] Preferably, in the above-mentioned gas diffusion electrode for in-situ efficient production of hydrogen peroxide, the model of the hydrophobic carbon paper is HCP020P.

[0013] Preferably, the carbon black model of the above-mentioned gas diffusion electrode for in-situ efficient production of hydrogen peroxide is VulcanXC-72.

[0014] The method for preparing a gas diffusion electrode for in-situ efficient production of hydrogen peroxide as described in any one of the above items comprises the following steps:

[0015] 1) Place the hydrophobic carbon paper in an acetone solution for ultrasonic treatment for 30 minutes, rinse it repeatedly with deionized water, soak it in 0.1 mol / L dilute hydrochloric acid for 15 minutes, wash it with deionized water until it is neutral, and dry it in a vacuum at 60°C for 24 hours;

[0016] 2) adding the mixed powder of g-C3N4 and carbon nanotubes to a mixed solution of 2 mL PTFE emulsion, 20 mL deionized water and 1 mL isopropanol, stirring and mixing with ultrasonic wave for 30 min, ultrasonically mixing the mixed solution into a paste, and evenly coating the mixed solution on one side of the hydrophobic carbon paper treated in step 1);

[0017] 3) mixing carbon black and PTFE emulsion, adding them to a mixed solution of 10 mL of deionized water and 1 mL of isopropanol, stirring and mixing with ultrasonic waves for 20 min, and coating the obtained emulsion on the other side of the hydrophobic carbon paper treated in step 1);

[0018] 4) The coated hydrophobic carbon paper was placed in an oven at 80° C., dried for 24 h, and annealed in a muffle furnace.

[0019] Furthermore, in the above-mentioned preparation method, in step 2), the preparation method of g-C3N4 is: using urea as a precursor, placing 15g of urea in a crucible with a lid, and calcining it in a muffle furnace to obtain a yellow powder, and grinding the powder to obtain g-C3N4 powder.

[0020] Furthermore, in the above-mentioned preparation method of g-C3N4, the calcination conditions are: temperature of 540-550°C, residence time of 4h, heating rate of 5-10°C min -1 .

[0021] Furthermore, in the above-mentioned preparation method, in step 2), the mass ratio of g-C3N4 to carbon nanotubes is (0-2):1.

[0022] Preferably, in the above-mentioned preparation method, in step 2), the mass ratio of g-C3N4 to carbon nanotubes is 1.

[0023] Furthermore, in the above preparation method, in step 3), the mass ratio of carbon black to PTFE emulsion is 1:5.

[0024] Furthermore, in the above preparation method, in step 4), the muffle furnace annealing conditions are: temperature of 340-360°C, residence time of 1h, heating rate of 5-10°C min -1 .

[0025] The gas diffusion electrode described in any one of the above items is used as or for preparing an electrochemical cathode for in-situ production of hydrogen peroxide.

[0026] Further, the above application method is as follows: the in-situ production of hydrogen peroxide by the gas diffusion electrode is carried out in a glass reactor, the glass reactor is placed in a constant temperature water bath stirrer, the constant temperature is 20°C, and a small magnetic particle is placed in the glass reactor for continuous stirring; a two-electrode system is adopted, the gas diffusion electrode is used as the working electrode, the platinum sheet electrode is used as the counter electrode, the electrolyte is a Na2SO4 solution with a pH of 2-9 and a concentration of 0.1M, and the constant current density is 8-16mA / cm 2 In situ hydrogen peroxide production was carried out under the conditions of a gas flow rate of 0.6 L / min and an electrolysis time of 90 min.

[0027] Preferably, in the above application, the electrolyte is a Na2SO4 solution with a pH of 3 and a concentration of 0.1M, and the constant current density is 14 mA / cm 2 .

[0028] The beneficial effects of the present invention are:

[0029] 1. The present invention uses hydrophobic carbon paper as a substrate, which has good electrical conductivity and can effectively transfer electrons; the surface of the carbon paper is usually uniform and flat, which is conducive to the formation of a gas diffusion layer and can ensure the uniform distribution of gas in the electrolyte liquid phase, thereby improving the efficiency of the oxygen reduction reaction.

[0030] 2. The composite is loaded on both sides of the carbon paper as a catalyst layer and a gas diffusion layer respectively through ultrasonic impregnation. Through the action of ultrasound, the mixed liquid can fully penetrate and cover every microstructure on the electrode surface, ensuring that the coating and modification layer on the surface of the material has a uniform thickness and distribution; and the ultrasonic impregnation method is easy to operate and takes a short time, and can achieve uniform impregnation or coverage of the material in a relatively short time; the mechanical vibration of ultrasound can effectively increase the specific surface area of ​​the material, expose more active sites, thereby increasing the reaction rate and enhancing the electrochemical performance of the electrode.

[0031] 3. The present invention adopts a gas diffusion electrode as a cathode, and constructs a gas-liquid-solid three-phase composite "sandwich" cathode composed of a catalyst layer, a carbon paper substrate and a gas diffusion layer. The special design of the electrode surface reduces mass transfer resistance, enhances electrochemical efficiency, and realizes efficient in-situ production of hydrogen peroxide. After 1.5 hours, the hydrogen peroxide output can reach 1050 mg / L, the current efficiency is 76%, and the energy consumption is 5.56 KWh / Kg, that is, while maintaining the hydrogen peroxide yield, it can also maintain a high current efficiency. The unmodified electrode has a hydrogen peroxide output of 600 mg / L after 1.5 hours, and a current efficiency of 25%. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The present invention provides a flow chart for preparing a gas diffusion electrode for in-situ efficient production of hydrogen peroxide.

[0033] Figure 2 This is a graph showing the yield of hydrogen peroxide obtained at different mass ratios of g-C3N4 to carbon nanotubes in Example 1.

[0034] Figure 3 This is a graph showing the production of hydrogen peroxide obtained by the gas diffusion electrode at different current densities in Example 2.

[0035] Figure 4 This is a graph showing the production of hydrogen peroxide obtained by the gas diffusion electrode at different pH values ​​in Example 3.

[0036] Figure 5 This is a graph of current efficiency and energy consumption corresponding to different mass ratios of g-C3N4 and carbon nanotubes in Example 1.

[0037] Figure 6 This is a graph of current efficiency and energy consumption corresponding to the gas diffusion electrode at different current densities in Example 2.

[0038] Figure 7 This is a graph showing the current efficiency and energy consumption of the gas diffusion electrode at different pH values ​​in Example 3. DETAILED DESCRIPTION

[0039] The present invention will be further described in detail below in conjunction with specific embodiments, which are shown in the accompanying drawings. The embodiments described with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and cannot be interpreted as limiting the present invention.

[0040] The present invention adopts an electric Fenton reaction device to detect the performance of the prepared gas diffusion electrode. A platinum sheet electrode (2cm×2cm) is installed in the electric Fenton device as an anode and a gas diffusion electrode as a cathode to improve the performance of the gas diffusion electrode in electrocatalytic production of hydrogen peroxide.

[0041] Example 1

[0042] like Figure 1 As shown, the hydrophobic carbon paper was ultrasonically treated in an acetone solution for 30 minutes, rinsed repeatedly with deionized water, and then soaked in 0.1 mol / L dilute hydrochloric acid for 15 minutes, washed with deionized water until neutral, and vacuum dried at 60°C for 24 hours; 15 g of urea was placed in a crucible with a lid, and heated at 550°C in a muffle furnace for 4 hours (the heating rate was 5-10°C min -1) to obtain a yellow powder (graphite phase carbon nitride g-C3N4), which is ground into powder for later use. Take a mixed powder of g-C3N4 and carbon nanotubes in different mass ratios, add it to a mixed solution (2mL PTFE emulsion, 20mL deionized water and 1mL isopropanol), stir and mix with ultrasound for 30 minutes, ultrasonically mix the mixed solution into a paste, and evenly coat it on one side of the hydrophobic carbon paper. Prepare a mixed solution of carbon black and PTFE (polytetrafluoroethylene) emulsion with a mass ratio of 1:5, add 10mL deionized water and 1mL isopropanol, stir and mix with ultrasound for 20 minutes, coat the obtained emulsion on the other side of the hydrophobic carbon paper, place the coated hydrophobic carbon paper in an 80℃ oven, dry for 24 hours, and anneal at 360℃ in a muffle furnace for 1 hour (heating rate is 5~10℃min -1 ), and obtain a gas diffusion electrode.

[0043] According to the doping mass ratio of g-C3N4 to carbon nanotubes, the modified electrodes were recorded as CNTs@CP (the mass ratio of g-C3N4 to carbon nanotubes was 0), 0.5@CP (the mass ratio of g-C3N4 to carbon nanotubes was 0.5), 1.0@CP (the mass ratio of g-C3N4 to carbon nanotubes was 1), 1.5@CP (the mass ratio of g-C3N4 to carbon nanotubes was 1.5) and 2.0@CP (the mass ratio of g-C3N4 to carbon nanotubes was 2) electrodes.

[0044] The performance test of the electrode in situ production of hydrogen peroxide was carried out in a glass reactor. The electro-Fenton glass reactor was placed in a constant temperature water bath stirrer at a constant temperature of 20°C, and a small magnetic particle was placed in the glass reactor for continuous stirring. A two-electrode system was used, with a gas diffusion electrode as the working electrode and a platinum sheet electrode as the counter electrode. A DC power supply was used to provide a stable current. The electrolyte was 180 mL of a 0.1M Na2SO4 solution. The pH of the solution was adjusted to 3 with 0.05M H2SO4 and 0.05M NaOH. The constant current density was 14 mA / cm 2 In situ production of hydrogen peroxide was carried out under the conditions of a gas flow rate of 0.6 L / min and an electrolysis time of 90 min. Figure 2 and 5 As shown, the final results show that when the mass ratio of g-C3N4 to carbon nanotubes is 1, the hydrogen peroxide content in the measured solution is the highest, with a concentration of 1050 mg / L, and the current efficiency can reach 76%.

[0045] The production and current efficiency of hydrogen peroxide measured by the gas diffusion electrode of Example 1 are as follows: Figure 2 and 5As shown in the figure, compared with other control groups, different mass ratios of g-C3N4 and carbon nanotubes have a greater impact on the production of hydrogen peroxide. When the mass ratio of g-C3N4 to carbon nanotubes is 1-1.5, the amount of H2O2 generated increases rapidly; when the mass ratio of g-C3N4 to carbon nanotubes is >1.5, although H2O2 shows an increasing trend, the amount generated is much less than the amount generated when the mass ratio of g-C3N4 to carbon nanotubes is 1-1.5. Studies have shown that appropriate g-C3N4 can enhance the oxygen reduction reaction, significantly increase the production of H2O2, and improve the catalytic performance of the electrode. However, excessive g-C3N4 will distort the graphite lattice, resulting in structural defects, thereby reducing the conductivity of the material and affecting the electron transfer process. Compared with other modified electrodes, the gas diffusion electrode 1.0@CP has the highest hydrogen peroxide production, with a concentration of 1050 mg / L and a current efficiency of 76%.

[0046] Example 2

[0047] like Figure 1 As shown, the hydrophobic carbon paper was ultrasonically treated in an acetone solution for 30 minutes, rinsed repeatedly with deionized water, and then soaked in 0.1 mol / L dilute hydrochloric acid for 15 minutes, washed with deionized water until neutral, and vacuum dried at 60°C for 24 hours; 15 g of urea was placed in a crucible with a lid, and heated at 550°C in a muffle furnace for 4 hours (the heating rate was 5-10°C min -1 ) to obtain a yellow powder (graphite phase carbon nitride g-C3N4), which is ground into powder for later use. Take a mixed powder of g-C3N4 and carbon nanotubes with a mass ratio of 1, add it to a mixed solution (2mL PTFE emulsion, 20mL deionized water and 1mL isopropanol), stir and mix with ultrasound for 30 minutes, ultrasonically mix the mixed solution into a paste, and evenly coat it on one side of the hydrophobic carbon paper. Prepare a mixed solution of carbon black and PTFE (polytetrafluoroethylene) emulsion with a mass ratio of 1:5, add 10mL deionized water and 1mL isopropanol, stir and mix with ultrasound for 20 minutes, coat the obtained emulsion on the other side of the hydrophobic carbon paper, place the coated hydrophobic carbon paper in an 80°C oven, dry for 24 hours, and anneal at 360°C in a muffle furnace for 1 hour (heating rate is 5-10°C min -1 ), and obtain a gas diffusion electrode.

[0048] The performance test of the electrode in situ production of hydrogen peroxide was carried out in a glass reactor. The electro-Fenton glass reactor was placed in a constant temperature water bath stirrer with a constant temperature of 20°C. A small magnetic particle was placed in the glass reactor for continuous stirring. A two-electrode system was used, with a gas diffusion electrode as the working electrode and a platinum electrode as the counter electrode. A DC power supply was used to provide a stable current. The electrolyte was 180 mL of a 0.1 M Na2SO4 solution. The pH of the solution was adjusted to 3 with 0.05 M H2SO4 and 0.05 M NaOH. The gas flow rate was 0.6 L / min, the electrolysis time was 90 min, and the current density was 8 mA / cm 2 , 10mA / cm 2 , 12mA / cm 2 , 14mA / cm 2 , 16mA / cm 2 In situ generation of hydrogen peroxide is carried out under the conditions of Figure 3 and 6 As shown in the final results, when the current density is 14mA / cm 2 When the hydrogen peroxide content in the measured solution is the highest, the concentration is 1050 mg / L, and the current efficiency can reach 76%.

[0049] The production and current efficiency of hydrogen peroxide measured in Example 2 are as follows: Figure 3 and 6 As shown in the figure, compared with other control groups, the change of current density during the reaction has a greater impact on the production of hydrogen peroxide. When the current density is 8-14 mA / cm 2 When the current density exceeds 14 mA / cm, the production of hydrogen peroxide increases with the increase of current density. This is because the current density directly affects the rate of electron transfer on the electrode, accelerates the electrochemical reaction rate, and thus increases the rate of hydrogen peroxide generation. 2 When the current density is 14 mA / cm2, the hydrogen peroxide generation rate is no longer increased. This may be because the high current density limits the diffusion of oxygen in the solution, resulting in a decrease in the rate of oxygen reduction reaction, which further causes a decrease in the rate of hydrogen peroxide generation. 2 When the hydrogen peroxide content in the measured solution is the highest, the concentration is 1050 mg / L, and the current efficiency can reach 76%.

[0050] Example 3

[0051] like Figure 1 As shown, the hydrophobic carbon paper was ultrasonically treated in an acetone solution for 30 minutes, rinsed repeatedly with deionized water, and then soaked in 0.1 mol / L dilute hydrochloric acid for 15 minutes, washed with deionized water until neutral, and vacuum dried at 60°C for 24 hours; 15 g of urea was placed in a crucible with a lid, and placed in a muffle furnace and heated at 550°C for 4 hours (the heating rate was 5-10°C min-1 ) to obtain a yellow powder (graphite phase carbon nitride g-C3N4), which is ground into powder for later use. Take a mixed powder of g-C3N4 and carbon nanotubes with a mass ratio of 1, add it to a mixed solution (2mL PTFE emulsion, 20mL deionized water and 1mL isopropanol), stir and mix with ultrasound for 30 minutes, ultrasonically mix the mixed solution into a paste, and evenly coat it on one side of the hydrophobic carbon paper. Prepare a mixed solution of carbon black and PTFE (polytetrafluoroethylene) emulsion with a mass ratio of 1:5, add 10mL deionized water and 1mL isopropanol, stir and mix with ultrasound for 20 minutes, coat the obtained emulsion on the other side of the hydrophobic carbon paper, place the coated hydrophobic carbon paper in an 80°C oven, dry for 24 hours, and anneal at 360°C in a muffle furnace for 1 hour (heating rate is 5-10°C min -1 ), and obtain a gas diffusion electrode.

[0052] The performance test of the electrode in situ production of hydrogen peroxide was carried out in a glass reactor. The electro-Fenton glass reactor was placed in a constant temperature water bath stirrer at a constant temperature of 20°C, and a small magnetic particle was placed in the glass reactor for continuous stirring. A two-electrode system was used, with a gas diffusion electrode as the working electrode and a platinum electrode as the counter electrode. A DC power supply was used to provide a stable current. The electrolyte was 180 mL of a 0.1 M Na2SO4 solution. The pH of the solution was adjusted with 0.05 M H2SO4 and 0.05 M NaOH. The gas flow rate was 0.6 L / min, the electrolysis time was 90 min, and the current density was 14 mA / cm 2 In situ hydrogen peroxide production was performed under the conditions of 2, 3, 5, 7, and 9, respectively. Figure 4 and 7 As shown, the final results show that when the pH is 3, the hydrogen peroxide content in the measured solution is the highest, the concentration is 1050 mg / L, and the current efficiency can reach 76%.

[0053] The output and current efficiency of hydrogen peroxide measured in Example 3 are as follows: Figure 4 and 7As shown in the figure, compared with other control groups, the change of pH during the reaction has a greater impact on the production of hydrogen peroxide. When the pH is 2-3, the production of hydrogen peroxide increases with the increase of pH. This is because the pH value affects the charge state of the electrode surface, thereby affecting the adsorption of the reactant on the electrode surface and the electron transfer rate. Under acidic conditions, that is, low pH conditions, the reduction reaction of hydrogen peroxide is usually more favorable and faster. When the pH value exceeds 5, hydrogen peroxide no longer increases. This is because the change in pH value affects the concentration and type of ions in the electrolyte solution. These ions may directly participate in the reaction or affect the reaction rate. In the process of the solution changing from acid to alkaline, other competitive reaction paths will be promoted, resulting in a decrease in the amount of hydrogen peroxide generated. In the experiments with different pH values, when the pH value is 3, the hydrogen peroxide content in the measured solution is the highest, with a concentration of 1050 mg / L, and the current efficiency can reach 76%.

[0054] The gas diffusion electrode with in-situ efficient hydrogen peroxide production of the present invention has good stability and can maintain a high hydrogen peroxide production at a high cycle number.

[0055] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A gas diffusion electrode for in-situ efficient production of hydrogen peroxide, characterized in that: The gas diffusion electrode uses hydrophobic carbon paper as a substrate, and a catalyst layer and a gas diffusion layer are respectively loaded on both sides of the hydrophobic carbon paper; the catalyst layer is a mixed liquid prepared by mixing carbon nanotubes, g-C3N4, isopropanol, PTFE emulsion and water and loaded on one side of the hydrophobic carbon paper; the gas diffusion layer is a mixed liquid of carbon black and PTFE emulsion and loaded on the other side of the hydrophobic carbon paper.

2. The gas diffusion electrode for in-situ efficient production of hydrogen peroxide according to claim 1, characterized in that: The mass fraction of PTFE in the PTFE emulsion is 60%; the thickness of the hydrophobic carbon paper is 10-100 microns.

3. The gas diffusion electrode for in-situ efficient production of hydrogen peroxide according to claim 1, characterized in that: The model of the hydrophobic carbon paper is HCP020P; the model of the carbon black is Vulcan XC-72.

4. The method for preparing a gas diffusion electrode for in-situ efficient hydrogen peroxide production according to any one of claims 1 to 3, characterized in that: The steps include: 1) Place the hydrophobic carbon paper in an acetone solution for ultrasonic treatment for 30 minutes, rinse it repeatedly with deionized water, soak it in 0.1 mol / L dilute hydrochloric acid for 15 minutes, wash it with deionized water until it is neutral, and dry it in a vacuum at 60°C for 24 hours; 2) adding the mixed powder of g-C3N4 and carbon nanotubes to a mixed solution of 2 mL PTFE emulsion, 20 mL deionized water and 1 mL isopropanol, stirring and mixing with ultrasonic wave for 30 min, ultrasonically mixing the mixed solution into a paste, and evenly coating the mixed solution on one side of the hydrophobic carbon paper treated in step 1); 3) mixing carbon black and PTFE emulsion, adding them to a mixed solution of 10 mL of deionized water and 1 mL of isopropanol, stirring and mixing with ultrasonic waves for 20 min, and coating the obtained emulsion on the other side of the hydrophobic carbon paper treated in step 1); 4) The coated hydrophobic carbon paper was placed in an oven at 80° C., dried for 24 h, and annealed in a muffle furnace.

5. The preparation method according to claim 4, characterized in that: In step 2), the preparation method of g-C3N4 is: using urea as a precursor, placing 15 g of urea in a crucible with a lid, and calcining it in a muffle furnace to obtain a yellow powder, and grinding the powder to obtain g-C3N4 powder.

6. The preparation method according to claim 4, characterized in that: In step 2), the mass ratio of g-C3N4 to carbon nanotubes is (0-2):1; in step 3), the mass ratio of carbon black to PTFE emulsion is 1:

5.

7. The preparation method according to claim 4, characterized in that: In step 4), the muffle furnace annealing conditions are: temperature of 340-360°C, residence time of 1h, heating rate of 5-10°C min -1 .

8. The preparation method according to claim 5, characterized in that: The calcination conditions are: temperature of 540-550°C, residence time of 4h, heating rate of 5-10°C min -1 .

9. Use of the gas diffusion electrode according to claim 1, 2 or 3 as or for preparing an electrochemical cathode for in-situ production of hydrogen peroxide.

10. The use according to claim 9, characterized in that The method is as follows: the in-situ production of hydrogen peroxide by a gas diffusion electrode is carried out in a glass reactor, the glass reactor is placed in a constant temperature water bath stirrer, the constant temperature is 20°C, a small magnetic particle is placed in the glass reactor for continuous stirring; a two-electrode system is adopted, the gas diffusion electrode is used as the working electrode, the platinum sheet electrode is used as the counter electrode, the electrolyte is a Na2SO4 solution with a pH of 2-9 and a concentration of 0.1M, and the constant current density is 8-16mA / cm 2 In situ hydrogen peroxide production was carried out under the conditions of a gas flow rate of 0.6 L / min and an electrolysis time of 90 min.

Citation Information

Cited By

  • Gas diffusion electrode capable of synchronously strengthening O2 transmission and H2O2 selectivity, preparation method and application

    CN116354461A

  • Carbon-based nitrogen-loaded composite gas diffusion electrode material and application thereof in degradation of antibiotics in water body

    CN121377238A

  • Boron etching modified gas diffusion electrode preparation method and in-situ hydrogen peroxide production application

    CN122235753A